2021
DOI: 10.1126/science.aba5511
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional superconductivity and anisotropic transport at KTaO 3 (111) interfaces

Abstract: The unique electronic structure found at interfaces between materials can allow unconventional quantum states to emerge. Here we report on the discovery of superconductivity in electron gases formed at interfaces between (111) oriented KTaO3 and insulating overlayers of either EuO or LaAlO3. The superconducting transition temperature, approaching 2.2 K, is about one order of magnitude higher than that of the LaAlO3/SrTiO3 system. Strikingly, similar electron gases at KTaO3 (001) interfaces remain normal down t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
197
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(237 citation statements)
references
References 61 publications
31
197
1
8
Order By: Relevance
“…Liu et al, confirmed the results with the discovery of superconducting PLD grown interfaces between (111)-oriented KTaO 3 and insulating overlayers of LaAlO 3 [256]. It was found that the superconductivity of this heterostructure exhibits a crystallographic direction dependence in contrast to 2DEGs at SrTiO 3 interfaces [9,254,255] and can be continuously tuned from superconducting into insulating states by applying a gate voltage [257].…”
Section: Bilayersmentioning
confidence: 64%
“…Liu et al, confirmed the results with the discovery of superconducting PLD grown interfaces between (111)-oriented KTaO 3 and insulating overlayers of LaAlO 3 [256]. It was found that the superconductivity of this heterostructure exhibits a crystallographic direction dependence in contrast to 2DEGs at SrTiO 3 interfaces [9,254,255] and can be continuously tuned from superconducting into insulating states by applying a gate voltage [257].…”
Section: Bilayersmentioning
confidence: 64%
“…All the arguments above go for these systems as well. Note that superconductivity found for KTaO 3 (111)/LaTiO 3 (111) and KTaO 3 (111)/EuO is strongly dependent on carrier density [65]. Besides, the absence of superconductivity in LaTiO 3 (100) related interfaces indicates the influence of larger polarity discontinuity in LaTiO 3 (111) related interfaces.…”
Section: Band Bending In Lao/stomentioning
confidence: 89%
“…LAO/STO provides a paradigmatic example for polar/nonpolar interface and similar polar/nonpolar oxide heterostructures are LaTiO 3 /STO [60], KTaO 3 /STO [61], LaVO 3 /STO [62], LMO/SrMnO 3 [63], KTaO 3 /EuO [64], KTaO 3 (111)/LaTiO 3 (111) [65] and KTaO 3 (111)/EuO [65]. All the arguments above go for these systems as well.…”
Section: Band Bending In Lao/stomentioning
confidence: 99%
“…For perovskite KTaO 3 (KTO), some excellent properties have been observed, such as high mobilities and signatures of spin-orbit coupling in low-temperature magnetoresistance data [14], spin-charge conversion of 2DEG at KTO surface [15,16], spin-polarized 2DEGs at a mag- * Email: bgliu@iphy.ac.cn netic EuO/KTO interface [17], and 2D superconductivity discovered at the KTO-based oxide interfaces [18][19][20][21][22] (see [23] for an overall review). In view of realistic applications, a main challenge is the epitaxial growth of KTO because of very reactive potassium atoms.…”
Section: Introductionmentioning
confidence: 99%